Designing the Threshold: A Close Reading of Olafur Eliasson’s Approach to ‘Inside’ and ‘Outside’ - Dincer, Demet; Brejzek, Thea; Wallen, Lawrence (Interiority, 2019)
This article discusses Icelandic installation artist Olafur Eliasson’s approach of the threshold as a productive liminal space rather than as a static boundary between the inside and the outside. Often defined as the physical division between the interior and the exterior in architecture, the authors argue that by looking at Eliasson’s works in detail, the threshold’s inherent capacity of comprising a dynamic dialogue between inside and outside where one is determined by the other unfolds. This paper proposes that designing the relationships between inside and outside involves subtle renegotiations and redefinitions of conventionalised notions of their boundaries and a resultant emergence of new design strategies. Eliasson designs thresholds in diverse ways that he analyses and provokes the spatial associations between inside and outside, interior and exterior. While in Eliasson`s work the categories of inside and outside remain mutually exclusive, they physically co-exist at the same time; deliberately refracted, juxtapositioned, connected or confounded in an experimental yet rigorous approach that employs different scales and common characteristics. Seventeen of his works are analysed and grouped into four different threshold design strategies that result in an object, an association, an event and an immersive space.